Craft beers fermented by potential probiotic yeast or lacticaseibacilli strains promote antidepressant-like behavior in swiss webster mice - Silva, Larissa Cardoso (2018)
This study aimed to produce a probiotic-containing functional wheat beer (PWB) by an axenic culture system with potential probiotic Saccharomyces cerevisiae var boulardii 17 and probiotic-containing functional sour beer (PSB) by a semi-separated co-cultivation system with potential probiotic Lacticaseibacillus paracasei DTA 81 and Saccharomyces cerevisiae S-04. Additionally, results obtained from in vivo behavioral tests with Swiss Webster mice treated with PWB or PSB were provided, which is scarce in the current literature. Although the use of S. boulardii to produce beers is not a novelty, this study demonstrated that S. boulardii 17 performance on sugar wort stills not completely elucidated; therefore, further studies should be considered before using the strain in industrial-scale production. Co-culture systems with lacticaseibacilli strain and S. cerevisiae have been reported in the literature for PSB production. However, lacticaseibacilli survivability in beer can be improved by semi-separated co-cultivation systems, highlighting the importance of growing lacticaseibacilli in the wort before yeast pitching. Besides, kettle hopping must be chosen as the method for hop addition to produce PSB. The dry-hopping method may prevent iso-alpha formation in the wort; however, a tendency to sediment can drag cells at the tank bottom and negatively affect L. paracasei DTA 81 viability. Despite stress factors from the matrices and the stressful conditions encountered during GI transit, potential probiotic S. boulardii 17 and potential probiotic L. paracasei DTA 81 withstood at sufficient doses to promote antidepressant effects in the mice group treated with PWB or PSB, respectively.